2014
DOI: 10.1111/imj.12319
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiovascular risk in patients with severe mental illness

Abstract: Australians living with SMI have very high rates of cardiovascular risk factors, far in excess of the general Australian population and comparable with the ATSI population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
0
32
0
2
Order By: Relevance
“…Thirty studies were included for meta-analyses (Arango et al, 2008;Boden et al, 2013;Burghardt et al, 2014;Carr a et al, 2014;Centorrino et al, 2012;Cerit et al, 2008;Correll et al, 2014;Curtis et al, 2011;Elgamal et al, 2012;Gladigau et al, 2014;Gulec Oyekcin, 2009;Hatata et al, 2009;Holt et al, 2010;John et al, 2009;Keenan et al, 2013;Khatana et al, 2011;Kuzman et al, 2011;Lin et al, 2012;Mackin et al, 2007;MedeirosFerreira et al, 2013;Miller et al, 2013;Morgan et al, 2014;Pantusa et al, 2010;Risselada et al, 2012;Roshdy, 2011;Schorr et al, 2009;Steylen et al, 2009;Tseng et al, 2014;van Winkel et al, 2008;Wysokinski et al, 2012), using also unpublished data provided by corresponding authors (Boden et al, 2013;Burghardt et al, 2014;Carr a et al, 2014;Cerit et al, 2008;Correll et al, 2014;Curtis et al, 2011;Gladigau et al, 2014;Keenan et al, 2013;Kuzman et al, 2011;Lin et al, 2012;Mackin et al, 2007;<...>…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty studies were included for meta-analyses (Arango et al, 2008;Boden et al, 2013;Burghardt et al, 2014;Carr a et al, 2014;Centorrino et al, 2012;Cerit et al, 2008;Correll et al, 2014;Curtis et al, 2011;Elgamal et al, 2012;Gladigau et al, 2014;Gulec Oyekcin, 2009;Hatata et al, 2009;Holt et al, 2010;John et al, 2009;Keenan et al, 2013;Khatana et al, 2011;Kuzman et al, 2011;Lin et al, 2012;Mackin et al, 2007;MedeirosFerreira et al, 2013;Miller et al, 2013;Morgan et al, 2014;Pantusa et al, 2010;Risselada et al, 2012;Roshdy, 2011;Schorr et al, 2009;Steylen et al, 2009;Tseng et al, 2014;van Winkel et al, 2008;Wysokinski et al, 2012), using also unpublished data provided by corresponding authors (Boden et al, 2013;Burghardt et al, 2014;Carr a et al, 2014;Cerit et al, 2008;Correll et al, 2014;Curtis et al, 2011;Gladigau et al, 2014;Keenan et al, 2013;Kuzman et al, 2011;Lin et al, 2012;Mackin et al, 2007;<...>…”
Section: Study Selectionmentioning
confidence: 99%
“…The majority of studies (70%) were published over the last five years (Boden et al, 2013;Burghardt et al, 2014;Carr a et al, 2014;Centorrino et al, 2012;Correll et al, 2014;Curtis et al, 2011;Elgamal et al, 2012;Gladigau et al, 2014;Holt et al, 2010;Keenan et al, 2013;Khatana et al, 2011;Kuzman et al, 2011;Lin et al, 2012;Medeiros-Ferreira et al, 2013;Miller et al, 2013;Morgan et al, 2014;Pantusa et al, 2010;Risselada et al, 2012;Roshdy, 2011;Tseng et al, 2014;Wysokinski et al, 2012), with the oldest published in 2007 (Mackin et al, 2007). All manuscripts but four e written in Dutch (Steylen et al, 2009), Italian (Pantusa et al, 2010), Spanish (Medeiros-Ferreira et al, 2013), and Turkish languages (Gulec Oyekcin, 2009), respectively e were in English.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 A full 50% of people with multiple sclerosis (MS), and 50% of people with motor neuron disease, suffer from depression. [13][14][15][16] Even when patients have no comorbid mental health issues, health professionals working in a variety of care settings, including physiotherapists, provide reassurance, psychological support, and education to reduce distress and promote behavioural change. 17 Physiotherapists in Australia are educated and have the skills to manage the physical needs of these patients, and they are trained to look for and recognize potential bio-psychosocial factors that may affect treatment.…”
mentioning
confidence: 99%
“…The consultation emerged from a recognition that there is a need for interventions for people at risk of developing long term conditions in the UK (DH, 2011;Royal College of Psychiatrists, 2013) and internationally (Chang and Lu, 2012;Gladigau et al, 2013). There is compelling evidence that people experiencing serious mental health problems are at increased risk from obesity (Meyer et al, 2008;Seeman, 2009) and long term conditions (Gladigau et al, 2013;Osborn et al, 2007). The relationship between serious mental health problems and long term physical health problems is bi-directional, however, Naylor et al, (2012) reported that people living with a physical long term condition are two to three times more likely to experience mental health problems.…”
Section: Introductionmentioning
confidence: 99%